Assessing the diet of North American Atlantic salmon (Salmo salar L.) off the West Greenland coast using gut content and stable isotope analyses. (5th April 2017) - Dixon, Heather J.; Dempson, J. Brian; Sheehan, Timothy F.; Renkawitz, Mark D.; Power, Michael
Abstract: Investigations on the marine feeding of Atlantic salmon ( Salmo salar L.) in the Northwest Atlantic are limited compared with the Northeast Atlantic. Climate‐induced changes to food webs in Atlantic salmon feeding areas have been noted, alongside increased mortality despite a cessation of most marine fisheries. As forage efficiency may be hampering survival, it was important to address this knowledge gap. Atlantic salmon were sampled at three sites on the West Greenland coast (Sisimiut, Nuuk and Qaqortoq) between 2009 and 2011. Gut content and stable isotope analyses were combined to assess spatial and temporal differences in feeding. Capelin ( Mallotus villosus ) dominated the diet at Nuuk and Qaqortoq, whereas boreoatlantic armhook squid ( Gonatus fabricii ) was the dominant prey at Sisimiut. Hyperiid amphipods ( Themisto spp.) and sand lance ( Ammodytes spp.) were also important. Significant differences were found among sites for both gut contents and stable isotope analyses, with fewer differences evident temporally. Dietary differences were also evident across larger scales, with little overlap demonstrated with Northeast Atlantic diets and the emergence of boreoatlantic armhook squid as an important prey item over time. Atlantic salmon diets are frequently anchored on one or two prey items, on which they appear to specialize, but they will diversify to consume other available pelagic prey. Thus, Atlantic salmon are an opportunistic, generalist predator within the pelagic food web. The variability evident in diet suggests that the limited data available are insufficient to appropriately understand potential vulnerabilities that the species may have to ecosystem changes, and suggest further research is needed.